Intestinal Parasitic Infestation in Children at Three Kindergartens in Medan, North Sumatera - Erliana Malik Miraza; Abdul Gani; Mardiana Karim Dj.; Iskandar Z. Lubis; Chairuddin P. Lubis (Indonesian Pediatric Society, 1992)
A descriptive cross sectional study on intestinal parasitic infestation was earned out among children of three kindergartens (Methodist, Dharma Wanita and Aisyiah) in Medan. Of 162 samples of feces examined mixed infestations with Ascaris lumbricoides and Trichuris trichiura was found in 14,25%, single infestations of Trichuris trichiuria in 14,2%, AScaris lumbricoides in 13,0%, H. nana in 1,2% and G. Iamblia in 0,6%. Hookworm infestation was not found among preschool children in all of those three kindergartens.